Accelerated, severe lupus nephritis benefits from treatment with honokiol by immunoregulation and differentially regulating NF‐κB/NLRP3 inflammasome and sirtuin 1/autophagy axis. Issue 10 (19th August 2020) - Yang, Shin‐Ruen; Hsu, Wan‐Han; Wu, Chung‐Yao; Shang, Hung‐Sheng; Liu, Feng‐Cheng; Chen, Ann; Hua, Kuo‐Feng; Ka, Shuk‐Man
Abstract: Using honokiol (HNK), a major anti‐inflammatory bioactive compound in Magnolia officinalis, we show a potent therapeutic outcome against an accelerated, severe form of lupus nephritis (ASLN). The latter may follow infectious insults that act as environmental triggers in the patients. In the current study, an ASLN model in NZB/W F1 mice was treated with HNK by daily gavage after onset of the disease. We show that HNK ameliorated the ASLN by improving renal function, albuminuria, and renal pathology, especially reducing cellular crescents, neutrophil influx, fibrinoid necrosis in glomeruli, and glomerulonephritis activity scores. Meanwhile, HNK differentially regulated T cell functions, reduced serum anti‐dsDNA autoantibodies, and inhibited NLRP3 inflammasome activation in the mice. The latter involved: (a) suppressed production of reactive oxygen species and NF‐κB activation‐mediated priming signal of the inflammasome, (b) reduced mitochondrial damage, and (c) enhanced sirtuin 1 (SIRT1)/autophagy axis activation. In conclusion, HNK represents a new drug candidate for acute, severe episodes of LN capable of alleviating renal lesions in ASLN mice by negatively regulating T cell functions and by enhancing SIRT1/autophagy axis‐lessened NLRP3 inflammasome activation.